2001
DOI: 10.1097/00007632-200103150-00029
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Intradural Disc Herniation

Abstract: Cervical intradural disc herniation is an extremely rare condition. The pathogenesis remains obscure. Only 16 cases have been reported in the literature, and there has been little discussion concerning the local pathology of the herniated portion. The pathogenesis of the disease in the patient reported here was considered to be the adhesion and fragility of dura mater and posterior longitudinal ligament. This was caused by hypertrophy, with chronic inflammation and ossification of the posterior longitudinal li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…As the first three cases of BSS caused by cervical disc herniation reported by Stookey 12 in 1928, we could find only 26 cases of BSS caused by cervical disc herniation in the literature. [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16] (Table 1). Among these 29 cases including ours, there were 20 male subjects and nine female subjects, whose ages ranged from 25-73 years (mean 45.6 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the first three cases of BSS caused by cervical disc herniation reported by Stookey 12 in 1928, we could find only 26 cases of BSS caused by cervical disc herniation in the literature. [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16] (Table 1). Among these 29 cases including ours, there were 20 male subjects and nine female subjects, whose ages ranged from 25-73 years (mean 45.6 years).…”
Section: Discussionmentioning
confidence: 99%
“…6 BSS was observed in 10 of these 17 cases of cervical intradural disc herniation. 11 With respect to the treatment, all patients underwent surgery after diagnosis. Six patients were treated by laminectomy or hemilaminectomy, three patients by anterior discectomy without interbody fusion, 14 patients by anterior discectomy with interbody fusion, two patients by anterior corpectomy and interbody fusion, one patient by anterior discectomy with interbody fusion and laminectomy and our own three patients by anterior foraminotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the four patients with OPLL had received cervical massage or manipulation and the remaining two patients had had neck pain for several months prior to the onset of paralysis. [23][24][25][26] In addition, other investigators reported several cases of acute myelopathy or paralysis caused by cervical disc herniation, which is also rare. [8][9][10][11] However, there have been no reports of OPLL in the cervical spine causing acute tetraplegia in patients in whom there was no preceding trauma or neurological symptoms, as in the current case.…”
Section: Spinal Cord Infarction With Chronic Compression a Tanida Et Almentioning
confidence: 99%
“…Surgery is indicated when nonoperative treatment fails or there is worsening of radiculopathy and/ or myelopathy [28,36]. Several procedures have been described for treatment of disc herniation and cervical spondylosis including anterior decompression, laminectomy, laminoplasty, instrumented anterior and posterior fusion by plates or screws [2-4, 6, 7, 10, 16, 17, 19, 22, 24, 29, 34, 38, 40, 45, 50].…”
Section: Introductionmentioning
confidence: 99%